Characteristics of the Fungal Communities and Co-occurrence Networks in Hazelnut Tree Root Endospheres and Rhizosphere Soil - Ma, Wenxu; Yang, Zhen; Liang, Lisong; Ma, Qinghua; Wang, Guixi; Zhao, Tiantian (Frontiers in Plant Science, 2021)
Hazelnut trees have gained economic value in China in recent years, with scaled planting and research having started later in China started later than in other countries. Conducting basic research on hazelnut trees requires studying their related microorganisms. Here, we used high-throughput DNA sequencing to quantify the fungal communities in the roots and their surrounding soil of four hazelnut species. Fungal diversity in the soil surrounding the roots was significantly higher than that in the roots; the soil surrounding the roots had more Mortierellomycota, and the fungal community compositions differed among the four hazelnut species. The roots, especially those of the Ping’ou trees (Corylus. heterophylla × Corylus. avellane), contain more ectomycorrhizal fungi. The co-occurrence networks in the soil surrounding the roots were more sophisticated and steadier than those in the roots, even when the roots had higher modularity, because the structural differentiation of the roots differed from that of the surrounding soil. The natural connectivity of the microbial network revealed that the co-occurrence network of the soil was more stable. Two-factor correlation network analysis and linear regression analysis showed that the total organic carbon was the main environmental factor limiting the fungal communities. Our study revealed the community compositions, function prediction and co-occurrence network structural characteristics of fungi in hazelnut roots and their surrounding soil. We also examined the potential keystone taxa, and analyzed the environmental factors of the dominant fungal community compositions. This study provides guidance for managing hazelnut planting and provides insight for using and developing fungi in hazelnut roots and their surrounding soil.